2012
DOI: 10.4158/ep11269.or
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Circulating 25-Hydroxyvitamin D and bone Mineral Density in Young Physicians

Abstract: Objective To examine determinants of serum 25-hydroxyvitamin D [25(OH)D] and bone mineral density (BMD) in young physicians, a group not well studied previously. Methods We analyzed data from a questionnaire completed by young physicians as well as results of serum 25(OH)D, serum parathyroid hormone, and BMD measurements. Results Among 104 study subjects, 42% were white, 46% were Asian, 12% were “other” (10 Hispanic and 2 African American subjects), and 75% were women. The mean age and body mass index (BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Underground miners50Zonguldak, Turkey (41°45′N)Cross-sectional24.5 ± 28.22. Surface workers5035.3 ± 29.3Healthcare StudentsMaeda (2007) [108]Medical students44Sao Paulo (23° 34′S), BrazilDescriptive81.5 ± 35.8Gonzalez-Padilla (2011) [117]Medical students103Gran Canaria, Canary Islands (27°92′N)Descriptive69.6 ± 31.0<75 nmol/L: 28.6%<50 nmol/L: 32.6%Paper reported unit as ng/dL but ng/ml was used for calculationKaehler (2012) [118]Female healthcare professional students215Innsbruck, Austria (47°27′N)Cross-sectional50.3 ± 16.6<75 nmol/L: 33.5%<50 nmol/L: 55.8%Al-Elq (2012) [119]Medical students198Dammam, Saudi Arabia (26°39′N)Cross-sectional21.2 ± 11.9<75 nmol/L: 4%<50 nmol/L: 96%Manickam (2012) [120]Medical students and residents104Chicago, IL, USA (42°N)Descriptive54.0 ± 28.0<75 nmol/L: 77%Zabihiyeganeh (2014) [121]Medical students100Tehran, Iran (35° 69′N)Cross-sectional42.0 ± 11.7<75 nmol/L: 15%<50 nmol/L: 84%Milovanovic (2015) [122]Medical, pharmacy and dental students86Kragujevac, Serbia (44°N)Descriptive33.1 ± 12.1<50 nmol/L: 88.4%Medical ResidentsHaney (2004) [61]Medical residents34Portland, OR, USA (45°52′ N)Interrupted series56.4 ± 20.1<50 nmol/L: 38%Paper reported unit as ng/dL but ng/ml was used for calculationMaeda (2007) [108]Medical residents49Sao Paulo, Brazil (23° 34′S)Descriptive67.1 ± 27.0Orlandin Premaor (2014) [123]Medical residents73Porto Alegre, Brazil (30°S)Cross-sectional44.7 ± 20.0<50 nmol/L: 57.4%…”
Section: Resultsmentioning
confidence: 99%
“…Underground miners50Zonguldak, Turkey (41°45′N)Cross-sectional24.5 ± 28.22. Surface workers5035.3 ± 29.3Healthcare StudentsMaeda (2007) [108]Medical students44Sao Paulo (23° 34′S), BrazilDescriptive81.5 ± 35.8Gonzalez-Padilla (2011) [117]Medical students103Gran Canaria, Canary Islands (27°92′N)Descriptive69.6 ± 31.0<75 nmol/L: 28.6%<50 nmol/L: 32.6%Paper reported unit as ng/dL but ng/ml was used for calculationKaehler (2012) [118]Female healthcare professional students215Innsbruck, Austria (47°27′N)Cross-sectional50.3 ± 16.6<75 nmol/L: 33.5%<50 nmol/L: 55.8%Al-Elq (2012) [119]Medical students198Dammam, Saudi Arabia (26°39′N)Cross-sectional21.2 ± 11.9<75 nmol/L: 4%<50 nmol/L: 96%Manickam (2012) [120]Medical students and residents104Chicago, IL, USA (42°N)Descriptive54.0 ± 28.0<75 nmol/L: 77%Zabihiyeganeh (2014) [121]Medical students100Tehran, Iran (35° 69′N)Cross-sectional42.0 ± 11.7<75 nmol/L: 15%<50 nmol/L: 84%Milovanovic (2015) [122]Medical, pharmacy and dental students86Kragujevac, Serbia (44°N)Descriptive33.1 ± 12.1<50 nmol/L: 88.4%Medical ResidentsHaney (2004) [61]Medical residents34Portland, OR, USA (45°52′ N)Interrupted series56.4 ± 20.1<50 nmol/L: 38%Paper reported unit as ng/dL but ng/ml was used for calculationMaeda (2007) [108]Medical residents49Sao Paulo, Brazil (23° 34′S)Descriptive67.1 ± 27.0Orlandin Premaor (2014) [123]Medical residents73Porto Alegre, Brazil (30°S)Cross-sectional44.7 ± 20.0<50 nmol/L: 57.4%…”
Section: Resultsmentioning
confidence: 99%
“…These conflicting results could be due to various reasons . One study in Chicago measured the serum 25OHD levels and BMD in 104 young physicians and found that vitamin D insufficiency and a low BMD could be important contributors to future osteoporotic fractures . The present study showed that low serum 25OHD levels were associated with low BMD and high disease activity in RA.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 36% of healthy young adults and up to 57% of general medicine inpatients in the USA suffer from vitamin D inadequacy. These figures are even higher in Europe . According to reports that have been published in China since 2000, vitamin D deficiency and insufficiency were widespread and prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…Serum 25(OH)D was measured by a direct, competitive- type chemiluminescence immunoassay (CLIA) original assay (Liaison, DiaSorin, Stillwater, MN, USA) (21,22). The intra- and inter-assay coefficients of variability (CVs) were 10.8% and 13.9%, respectively.…”
Section: Methodsmentioning
confidence: 99%